Sex matters: predator presence induces sexual dimorphism in a monomorphic prey, from stress genes to morphological defences. (8th December 2022) - Vinterstare, Jerker; Brönmark, Christer; Nilsson, P Anders; Langerhans, R Brian; Chauhan, Pallavi; Hansson, Bengt; Hulthén, Kaj
Abstract: Inducible defences allow prey to increase survival chances when predators are present while avoiding unnecessary costs in their absence. Many studies report considerable inter-individual variation in inducible defence expression, yet what underlies this variation is poorly understood. A classic vertebrate example of a predator-induced morphological defence is the increased body depth in crucian carp ( Carassius carassius ), which reduces the risk of predation from gape-size limited predators. Here, we report that among-individual variation in morphological defence expression can be linked to sex. We documented sexual dimorphism in lakes in which crucian carp coexisted with predators, where females showed shallower relative body depths than males, but not in a predator-free lake. When exposing crucian carp from a population without predators to perceived predation risk in a laboratory environment (presence/absence of pike, Esox lucius ), we found that males expressed significantly greater morphological defence than females, causing sexual dimorphism only in the presence of predators. We uncovered a correlative link between the sex-specific inducible phenotypic response and gene expression patterns in major stress-related genes ( POMC, MC3R, and MC4R ). Together, our results highlight that sex-specific responses may be an important, yet underappreciated, component underlying inter-individual differences in the expression of inducible defences, even in species without pronounced sexual dimorphism.